Implementation Of Singing Method In English Language Learning On Memory Of Grade 1 Students At SD II Muslim Madani In The 2024/2025 Academic Year - Ida Handayani; M. Arzani; Muh. Hamdani (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to describe the implementation of the singing method in language learning and the supporting and inhibiting factors of applying the singing method in English language learning on the memory of first-grade students in the 2024/2025 academic year. The research was conducted at SD Islam Integrasi Muslim Madani, Gubuk Baru Tanjung, involving 25 first-grade students in the second semester of the 2024/2025 academic year. This study is qualitative research, with data obtained from observations, interviews, and documentation. This research discusses the implementation of the singing method in English language learning to enhance the memory of first-grade students at SDII Muslim Madani, as well as the supporting and inhibiting factors influencing it. The results indicate that the singing method is highly effective in improving students’ memory, learning motivation, and English proficiency, particularly through structured steps such as material preparation, song repetition, the use of visual media, and active student engagement. Support from the school, availability of facilities, and the creative role of teachers are key factors in the success of this method. Meanwhile, challenges include time constraints, inadequate audio facilities, and varying student interests and abilities. However, these obstacles can be overcome with appropriate strategies, such as forming small groups and utilizing personal devices. Overall, the singing method is a fun and effective learning strategy for enhancing English language skills at the elementary education level.